Republic of Korea-Indonesia Relations: Middle Power Diplomacy in East Asia - Poetri, Devi Anggraeni; Govindasamy, Geetha; Md Akhir, Md Nasrudin (WILAYAH: The International Journal of East Asian Studies, 2018)
This article analyzes how middle powers can contribute to regional peace and stability by examining the Republic of Korea – Indonesia relations in East Asia. The article suggests that there are potential contributions of like-minded middle power relations in regional governance amidst regional challenges. This is reflected by the extent to which these middle powers manoeuvre major problems in East Asia through various forms of regional institutions. By engaging with ASEAN, while trying to maintain good relations with the United States and China, the Republic of Korea and Indonesia are able to influence as well as promote regional peace and stability.